Implementasi Kepemimpinan Spiritual Kepala Madrasah dalam Mewujudkan Kedisiplinan Siswa Kelas X MA Abu Amr Pasuruan - Afif Mochamad Hilmi; Ashari Ashari (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This research method uses descriptive qualitative research. Data collection techniques use observation, interviews and documentation. The data analysis technique uses data collection, reduction, display and verification. Meanwhile, data validity testing uses triangulation of sources, techniques and time. The research results show that 1) The concept of spiritual leadership of the madrasa head in realizing student discipline is a household concept. In a household, trust, commitment, responsibility, and full affection and sincerity are needed; 2) the implementation of the madrasah head's spiritual leadership in realizing student discipline is by articulating a vision, learning programs, non-academic programs, programs in the field of spiritual development activities.